2001
DOI: 10.1385/ep:12:3:355
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Granulomatous Inflammation Associated with Adenoma of Parathyroid Gland Manifesting as Primary Hyperparathyroidism

Abstract: A 36-year-old female presented with generalized bone pain, muscular weakness and enlarged cervical lymph nodes. The biochemical findings and skeletal survey was suggestive of primary hyperparathyroidism (PHPT). CT of neck and thorax showed enlarged multiple lymph nodes in the cervical and superior mediastinal region. With a diagnosis of PHPT she underwent cervical exploration and excision of enlarged right inferior parathyroid gland along with biopsy of nodes were done. Histopathology revealed the features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…In these latter cases, the parathyroid glands had been demonstrated to be infiltrated by granulomatous inflammation of tuberculosis within parathyroid adenomas. In the report from India and in a recent report from England, in addition to granulomatous inflammation of the parathyroid adenoma, inflammation of the lymph nodes had been detected [7,9]. Our patient showed no pathology in the lymph nodes on either pathological examination or imaging, although her two excised lymph nodes showed findings consistent with reactive hyperplasia.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In these latter cases, the parathyroid glands had been demonstrated to be infiltrated by granulomatous inflammation of tuberculosis within parathyroid adenomas. In the report from India and in a recent report from England, in addition to granulomatous inflammation of the parathyroid adenoma, inflammation of the lymph nodes had been detected [7,9]. Our patient showed no pathology in the lymph nodes on either pathological examination or imaging, although her two excised lymph nodes showed findings consistent with reactive hyperplasia.…”
Section: Discussionsupporting
confidence: 52%
“…Hypercalcemia due to co-existing parathyroid adenoma and sarcoidosis had been published before in the literature [3-6]; however, few cases of granulomatous inflammation within the parathyroid adenoma had been reported [7-9]. In these latter cases, the parathyroid glands had been demonstrated to be infiltrated by granulomatous inflammation of tuberculosis within parathyroid adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This patient did not have any other focus of tuberculosis. Tuberculosis of the parathyroid gland is extremely rare and the literature on this entity is limited to a few case reports [10, 11]. To the best of our knowledge, there is no literature in the English language on the ultrasound appearance of tuberculosis of the parathyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Kinoshita et al (11) reported a patient who was on steroid therapy for sarcoidosis and who later developed a parathyroid adenoma. Others have reported tuberculous granulomatous inflammation (12) and necrotizing granulomatous inflammation (13) associated with parathyroid adenoma. However, all these patients—unlike the present case—had manifestations of primary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%